2019
DOI: 10.1128/jvi.00240-19
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted CXCR2 Signaling in Oligodendroglia Lineage Cells Enhances Myelin Repair in a Viral Model of Multiple Sclerosis

Abstract: CXCR2 is a chemokine receptor expressed on oligodendroglia that has been implicated in the pathogenesis of neuroinflammatory demyelinating diseases as well as enhancement of the migration, proliferation, and myelin production by oligodendroglia. Using an inducible proteolipid protein (Plp) promoter-driven Cre-loxP recombination system, we were able to assess how timed ablation of Cxcr2 in oligodendroglia affected disease following intracranial infection with the neurotropic JHM strain of mouse hepatitis virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…Both are ligands of CXCR2, which is involved in the differentiation and migration of oligodendrocyte precursors, and whose disruption enhances remyelination in a mouse model. 32 This interpretation has the encouraging implication that it should be possible to target this neural plasticity therapeutically, independently from immunomodulatory treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Both are ligands of CXCR2, which is involved in the differentiation and migration of oligodendrocyte precursors, and whose disruption enhances remyelination in a mouse model. 32 This interpretation has the encouraging implication that it should be possible to target this neural plasticity therapeutically, independently from immunomodulatory treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the co-culture of SCs and ECs led to an obvious growth of DRG axons. In addition, NGF also has a certain promoting effect on the growth and proliferation of SCs, which may further accelerate the growth and repair of nerves [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to stimulate the maturation of OPCs to myelinating oligodendrocytes are ongoing yet successful translation to effective and sustained therapies has yet to occur. Research from our laboratory and others has shown CXCR2 signaling on oligodendroglia impacts remyelination potentially by augmenting OPC maturation (Liu et al, 2015b;Marro et al, 2019). OPC differentiation into mature myelinating oligodendrocytes is a complex process that is regulated by activation and repression of specific growth and transcription factors as well as epigenetic factors (Tauheed et al, 2016;Santos et al, 2018;Tiane et al, 2019).…”
Section: Perspectivesmentioning
confidence: 99%
“…We recently employed a similar approach by generating Plp-Cre-ER(T); Cxcr2 fl/f transgenic mice (Cxcr2-CKO mice) in which Cxcr2 was conditionally ablated upon tamoxifen treatment in adult mice (Marro et al, 2019) (Fig. 1, Fig.…”
Section: Oligodendroglia and Cxcr2 Signalingmentioning
confidence: 99%